(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Ancient mythology, regional folklore, and dastans provide the groundwork for Uzbekistan’s cultural and moral identity. These fables combine Zoroastrianism, Tengriism, and Islamic philosophy to teach morality and societal standards. The miraculous births and supernatural interventions of heroes like Alpomish and Goroghli relate morality to holy beginnings and cosmic equilibrium while promoting bravery, loyalty, and community. This study uses archetypal criticism (Jung; Campbell), functionalism (Malinowski), and cultural memory theory (Assmann; Reichl) to examine how Uzbek myths and epics justify social order, preserve communal memory, and transmit values like justice (adolat), bravery (mardlik), wisdom (donolik), and honor (nomus). Epics mix pre-Islamic elements with Islamic ideals via the bakhshi’s performance and preservation of heritage. These mythical heroes have been resurrected as national emblems of power, justice, and togetherness since independence, tying contemporary statehood to a mythical past. Uzbek oral epics show how story can hold cultural memory and change ethics across generations.